Analysis of statistical projects designed by future Early Childhood Education teachers (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this study we analyse the statistical projects proposed by future pre-school teachers when they want to tackle the resolution of statistical problems. The aim of this study is to explore the knowledge that future pre-school teachers display when designing tasks for teaching statistics at this educational level. To this end, we have focused on the different stages (formulation of questions, data collection, data analysis and interpretation of results) that make up the process of solving statistical problems, as these are a tool to contribute to the development of statistical literacy from an early age. The data obtained show the need to address the different stages of statistical problem solving in the training of future Early Childhood Education teachers, because although they have a command of some of the aspects involved in the different stages, they leave out central aspects such as the variability of the data.
Keywords: Statistical projects; Statistical Literacy; Early Childhood Education; Future teachers